Assessment of Cd-induced genotoxic damage in Urtica pilulifera L. using RAPD-PCR analysis - ÖZYİĞİT, İBRAHİM İLKER (TAYLOR & FRANCIS LTD, 2016)
Plants can be used as biological indicators in assessing the damage done by bioaccumulation of heavy metals and their negative impact on the environment. In the present research, Roman nettle (Urtica pilulifera L.) was employed as a bioindicator for cadmium (Cd) pollution. The comparisons between unexposed and exposed plant samples revealed inhibition of the root growth (similar to 25.96% and similar to 45.92% after treatment with 100 and 200 mu mol/L Cd concentrations, respectively), reduction in the total soluble protein quantities (similar to 53.92% and similar to 66.29% after treatment with 100 and 200 mu mol/L Cd concentrations, respectively) and a gradual genomic instability when the Cd concentrations were increased. The results indicated that alterations in randomly amplified polymorphic DNA (RAPD) profiles, following the Cd treatments, included normal band losses and emergence of new bands, when compared to the controls. Also, the obtained data from F1 plants, utilized for analysis of genotoxicity, revealed that DNA alterations, occurring in parent plants due to Cd pollution, were transmitted to the next generation.
Keywords: RAPD-PCR; genotoxicity; cadmium (Cd); Roman nettle; heavy metals; AMPLIFIED POLYMORPHIC DNA; HEAVY-METALS; CADMIUM ACCUMULATION; PHOTOSYNTHESIS; TOLERANCE; ALUMINUM; SATIVUM; TOBACCO; GENOME; LEAVES